2018
DOI: 10.18203/2320-6012.ijrms20184873
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical profile of vitiligo in Ibadan, Nigeria

Abstract: Background: Vitiligo patients are seen routinely in the Dermatology Outpatient Clinic of the University College Hospital Ibadan, Nigeria. However, the epidemiologic and clinical profile of these patients is not documented. The aim of this study was to document the clinical (age of onset, location, severity, class of vitiligo) and sociodemographic characteristics of these patients. Methods: This is a retrospective descriptive study of patients treated for vitiligo from January 2005 to December 2009 at the Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Other studies have shown variation in the duration of vitiligo, e.g. less than 2 months (Suseno et al, 2018) and more than 1 year (Anaba, George, & Ogunbiyi, 2018).…”
Section: Clinical Overview Of Vitiligo Patientsmentioning
confidence: 94%
“…Other studies have shown variation in the duration of vitiligo, e.g. less than 2 months (Suseno et al, 2018) and more than 1 year (Anaba, George, & Ogunbiyi, 2018).…”
Section: Clinical Overview Of Vitiligo Patientsmentioning
confidence: 94%